x ∈ ( 0 , 2 π ) , c o s x = 3 1
m = 0 ∑ ∞ 3 m c o s m x =
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We need to find a pattern for cos m x , which can be given by the Chebyshev polynomials . On this helpful page we find that
cos m x = T m ( cos x )
as well as
∑ m = 0 ∞ T m ( z ) t m = 1 − 2 t z + t 2 1 − t z .
We substitute t = z = 3 1 :
∑ m = 0 ∞ 3 m cos m x = 1 − 2 ⋅ 3 1 ⋅ 3 1 + ( 3 1 ) 2 1 − 3 1 ⋅ 3 1 = 1 .
Problem Loading...
Note Loading...
Set Loading...
Think about the sum of a geometric sequence (e^ix/3)^m. Taking a real part of this sum, we get a result.